What Decides the Exchange Rate? Theory – and Predictions of the Norwegian Krone against the Euro - Vale, Per Halvor (Archives of Business Research, 2018)
The paper analyses changes in the exchange rate of the Norwegian krone (NOK) as measured against the Euro, with the purpose of forecasting future exchange rates. The analysis is based on an error correction model. The model is given an autoregressive form. From the model is derived “out-of-sample forecast”. The predictions are compared with forecasts obtained from a Random Walk model. The empirical findings show that even though the economic model identifies several important explanatory variables, the Random Walk model performs better.